2014
DOI: 10.3389/fnbot.2014.00006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of odor and body posture on perceived duration

Abstract: This study reports an examination of the internal clock model, according to which subjective time duration is influenced by attention and arousal state. In a time production task, we examine the hypothesis that an arousing odor and an upright body posture affect perceived duration. The experimental task was performed while participants were exposed to an odor and either sitting upright (arousing condition) or lying down in a relaxing chair (relaxing condition). They were allocated to one of three experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 40 publications
1
23
2
Order By: Relevance
“…For example, in the study by Tamm et al (2014), the duration judgment was performed on visual stimuli, whereas in this study time intervals were presented in an auditory modality within odor contexts. Schreuder et al (2014), investigating the effect of odor and body posture on a time production task for 1.33, 1.58, 2.17 min intervals, reported that when participants were exposed to arousing conditions they produced significantly shorter intervals than participants who were exposed to no odor. However, the physiological arousal measures and self-reports did not differ between the control and odor groups and this indicated that the perceived duration was not caused by increased arousal.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in the study by Tamm et al (2014), the duration judgment was performed on visual stimuli, whereas in this study time intervals were presented in an auditory modality within odor contexts. Schreuder et al (2014), investigating the effect of odor and body posture on a time production task for 1.33, 1.58, 2.17 min intervals, reported that when participants were exposed to arousing conditions they produced significantly shorter intervals than participants who were exposed to no odor. However, the physiological arousal measures and self-reports did not differ between the control and odor groups and this indicated that the perceived duration was not caused by increased arousal.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that when participants were exposed to an arousing odor (i.e., rosemary) they perceived shorter time intervals compared with a control condition without olfactory stimulation (Schreuder et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations